The effects of gasotransmiters gasotransmitters inhibition on homocysteine thiolactone acutely induced changes in oxidative stress markers in rat plasm - Djuric, Dragan M (Scripta Medica, 2019)
AbstractBackground: The importance of homocysteine (Hcy) is increasingly recognized in last few decades as anindependent risk factor for atherosclerosis and thrombosis, but there is lack of data referring to influenceof Hcy on plasma oxidative stress parameters as well as the role of gasotransmitters in these effects.Therefore, this study aim was to assess the role of gasotransmitter inhibitors in Hcy-induced effects onplasma oxidative stress in rats.Material and Methods: Study involved 96 male Wistar albino rats divided into 8 groups: 1) Controlgroup – saline (1ml 0.9 % NaCl i.p.,); 2) DL-Hcy (8 mmol/kg i.p. DL homocysteine (DL-Hcy)); 3) L-NAME (10 mg/kg i.p. N ω -Nitro-L-arginine methyl ester (L-NAME), inhibitor of NO production); 4)ZnPPR IX (30 mol/kg i.p. protoporphyrin IX zinc (ZnPPR IX), inhibitor of CO production); 5) DL-PAG(50 mg//kg i.p. DL-propargylglycine (DL-PAG), inhibitor of H 2 S production); 6) DL-Hcy+L-NAME (8mmol/kgi.p. DL-Hcy + 10 mg/kg i.p. L-NAME); 7) DL-Hcy+ZnPPR IX (8 mmol/kgi.p. DL-Hcy + 30mol/kg i.p. Zn PPR IX), and 8) DL-Hcy+DL-PAG (8 mmol/kg i.p. DL-Hcy + 50 mg//kg i.p. DL-PAG).In all experimental groups, tested substances were administered in a single dose, intraperitoneally, 60minutes before animals’ euthanasia. In the collected blood samples malondialdehyde concentration,catalase, glutathione peroxidase and superoxide dismutase activity were measured.Results: Applied substances induced rapid and strong increase of plasma antioxidant enzymatic activityprobably as a compensatory response to its pro-oxidant influence.Conclusion: The effects of Hcy on the activity of plasma antioxidant enzymes are in part mediated viainteraction with gasotransmitters.